The Mechanical Interplay Between Differentiating Mesenchymal Stem Cells and Gelatin-Based Substrates Measured by Atomic Force Microscopy - Meng, Hongxu; Chowdhury, Tina T.; Gavara, Núria (Frontiers in Cell and Developmental Biology, 2021)
Traditional methods to assess hMSCs differentiation typically require long-term culture until cells show marked expression of histological markers such as lipid accumulation inside the cytoplasm or mineral deposition onto the surrounding matrix. In parallel, stem cell differentiation has been shown to involve the reorganization of the cell’s cytoskeleton shortly after differentiation induced by soluble factors. Given the cytoskeleton’s role in determining the mechanical properties of adherent cells, the mechanical characterization of stem cells could thus be a potential tool to assess cellular commitment at much earlier time points. In this study, we measured the mechanical properties of hMSCs cultured on soft gelatin-based hydrogels at multiple time points after differentiation induction towards adipogenic or osteogenic lineages. Our results show that the mechanical properties of cells (stiffness, viscosity) and the organization of the actin cytoskeleton are highly correlated with lineage commitment. Most importantly, we also found that the mechanical properties and the topography of the gelatin substrate in the vicinity of the cells are also altered as differentiation progresses towards the osteogenic lineage, but not on the adipogenic case. Together, these results confirm the biophysical changes associated with stem cell differentiation and suggest a mechanical interplay between the differentiating stem cells and their surrounding extracellular matrix.